EFFORTS TO INCREASE HIGH-LEVEL THINKING ABILITY USING OPEN-ENDED APPROACHES - Hamimah; Kenedi, Ary Kiswanto; Zuryanty (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
The purpose of this study is to determine the increase in the higher-order thinking skills (HOTS) of PGSD students by using an open-ended approach. The study was quasi-experimental research with a non-equivalent control group design conducted in the PGSD UNP department. The results of this study stated that there were differences in the average N-Gain of HOTS of PGSD students who learned using the open-ended approach compared to students who learned using the conventional approach in the basic social studies concept subject. This research proved that there was a significant increase in students’ learning by using the open-ended approach compared to students learning with the conventional approach. The implications of this study can be used as an effort to improve students’ HOTS.